FLEXIBLE WORKING ARRANGEMENT: DOES REALLY GIVE JOB SATISFACTION TOWARD EMPLOYEE? - Ratri Nastiti, Prianka; Setyorini, Noni; Ervina I, Rr Hawik; Karina Putri, Noventia (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
This study aims to examine the impact of Flexible Working Arrangement (FWA) on employee job satisfaction with wellbeing as a mediating variable. Data processing techniques used SMART PLS 3.0, with mediation testing based on Hayes' process. The total number of respondents in this study was 108. The results of the study revealed that FWA does not have a direct influence on employee job satisfaction. However, after the mediation process, FWA does have an impact on job satisfaction through employee wellbeing. Based on this, the practical implication is that companies need to pay attention to the limitations of working hours and workload to ensure that flexible working hours do not make employees feel like they are working endlessly with unlimited time, so that employee wellbeing can be maintained, and job satisfaction can be achieved.